2010
DOI: 10.1080/03079451003604621
|View full text |Cite
|
Sign up to set email alerts
|

Development of a duplex real-time TaqMan PCR assay with an internal control for the detection ofMycoplasma gallisepticumandMycoplasma synoviaein clinical samples from commercial and backyard poultry

Abstract: In this study, we report the development and validation of a duplex real-time polymerase chain reaction (PCR) assay with an internal control using TaqMan-labelled probes for the detection of Mycoplasma gallisepticum and Mycoplasma synoviae (duplex MGMS PCR). The MGMS PCR was highly specific with a sensitivity of 7 and 1 colony-forming units/ml for M. gallisepticum and M. synoviae, respectively, using dilution of pure culture that corresponds to 34 and 29 DNA copies per reaction. Validation of the assay was com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
40
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 35 publications
1
40
1
Order By: Relevance
“…Recently, Fraga et al (2013) observed a problem in specificity when using conserved 16SrRNA gene primers for MS which detected Mycoplasma cloacale as well as MG and MS mixed infection in multiplex RT-PCR. Such non-specificity issues have not been reported for species-specific (mgc2 and vlhA genes) primers/probes (Raviv and Kleven 2009;Sprygin et al 2010). We determined specificity in the present study using in silico BLASTn analysis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, Fraga et al (2013) observed a problem in specificity when using conserved 16SrRNA gene primers for MS which detected Mycoplasma cloacale as well as MG and MS mixed infection in multiplex RT-PCR. Such non-specificity issues have not been reported for species-specific (mgc2 and vlhA genes) primers/probes (Raviv and Kleven 2009;Sprygin et al 2010). We determined specificity in the present study using in silico BLASTn analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We determined specificity in the present study using in silico BLASTn analysis. Furthermore, the method described by Sprygin et al (2010) incorporated avian Reo virus (S3 gene) as an internal control (IC) in a Real-time PCR assay (Table 1). In contrast, we successfully incorporated commercially available (ready to use) TaqMan ® Exo IPC to avoid false negative results that might happen due to failure in DNA extraction/PCR inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations